2015
DOI: 10.1016/j.mayocp.2015.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Monocyte Count and Lymphocyte-Monocyte Ratio Predict Outcome in Nodular Sclerosis Hodgkin Lymphoma: Evaluation Based on Data From 1450 Patients

Abstract: This study confirms that AMC has prognostic value in cHL that is particularly significant in patients with NS subtype histology. This finding links the known impact of macrophages and monocytes in Hodgkin lymphoma with routine clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 35 publications
0
42
1
Order By: Relevance
“…There is a body of evidence showing that the tumor microenvironment, host immunity, and systemic inflammatory responses are critical for determining the clinical course and outcome of patients with tumors . Using lymphocytes and monocytes as surrogate markers of tumor microenvironment and inflammatory responses, more and more studies have found that elevated absolute monocyte count (AMC), decreased absolute lymphocyte count (ALC), and the absolute lymphocyte to absolute monocyte count ratio (LMR) are predictors of various solid tumors, such as breast carcinoma, ovarian cancer, clonal cancer, and lung cancer, and similar findings have also been demonstrated in diffuse large B‐cell lymphoma (DLBCL) and classical Hodgkin's lymphoma (cHL) . In addition, parameters such as neutrophil‐lymphocyte ratio (NLR) and platelet‐lymphocyte ratio (PLR) have also exhibited prognostic activity in recent studies, although there were conflicting results .…”
Section: Introductionmentioning
confidence: 82%
“…There is a body of evidence showing that the tumor microenvironment, host immunity, and systemic inflammatory responses are critical for determining the clinical course and outcome of patients with tumors . Using lymphocytes and monocytes as surrogate markers of tumor microenvironment and inflammatory responses, more and more studies have found that elevated absolute monocyte count (AMC), decreased absolute lymphocyte count (ALC), and the absolute lymphocyte to absolute monocyte count ratio (LMR) are predictors of various solid tumors, such as breast carcinoma, ovarian cancer, clonal cancer, and lung cancer, and similar findings have also been demonstrated in diffuse large B‐cell lymphoma (DLBCL) and classical Hodgkin's lymphoma (cHL) . In addition, parameters such as neutrophil‐lymphocyte ratio (NLR) and platelet‐lymphocyte ratio (PLR) have also exhibited prognostic activity in recent studies, although there were conflicting results .…”
Section: Introductionmentioning
confidence: 82%
“…In HL, low ALC,1 high AMC,2 and low lymphocyte to monocyte ratios2, 7 are associated with a poor prognosis. However until now, only a few studies have analyzed the prognostic significance of ANC and NLR in patients with HL.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have considered the absolute lymphocyte count (ALC)1 as an important biomarker of tumor infiltrating lymphocytes, reflecting host immunity status, while absolute monocyte count (AMC)2 serves as a surrogate biomarker of tumor‐associated macrophages within the tumor microenvironment, and the absolute neutrophil count (ANC)3 as a measure of the systemic inflammatory response to malignancy. Inflammation is regarded as a critical component of tumor progression, and it is evident that the tumor microenvironment, is largely coordinated by inflammatory cells, which play a central role in the neoplastic process, promoting, proliferation, survival, and migration of tumor cell via activation of signaling pathways 4, 5, 6.…”
Section: Introductionmentioning
confidence: 99%
“…Immunity and inflammatory response impact the tumour microenvironment and malignancy progression (Mantovani et al , ). Metabolic and inflammatory parameters of the peripheral blood, and ratios of the latter, correlate with outcome in lymphoma patients (Tadmor et al , ). There is evidence outlining the prognostic significance of inflammation‐based scores including the Glasgow prognostic score (GPS; integrating serum C‐reactive protein and albumin), platelet‐to‐lymphocyte ratio (PLR) and neutrophil‐to‐lymphocyte ratio (NLR).…”
Section: Progression‐free and Overall Survival In Univariate Analysismentioning
confidence: 99%